Pengaruh Promosi, Pendapatan, Citra Merek Terhadap Keputusan Pembelian Tiket Lomba Burung Kicau - Maulana, Satriyo; Adelia, Vita; Purwanto, Dedik; Firdaus; Amelia; Yusuf, Ilham (Business Perspective Journal, 2024)
This research aims to analyze and describe the influence of promotion, income, and brand image on the decision to purchase tickets for the Indonesian Kuby bird competition in Semarang. The population in this study were participants in the Kuby Cup bird competition. The sample used in this research was 100 people. Data analysis was carried out using ordinal logistic regression analysis with SPSS 27. The results of this research analysis show that the promotion variable has a positive influence on purchasing decisions, the income variable has an influence on purchasing decisions, the brand image variable has an influence on purchasing decisions, and the promotion, income and brand image variables simultaneously influence purchasing decisions. Keywords: promotion, revenue, brand image, purchasing decisions